Cucumber (Cucumis sativus L.) Nitric Oxide Synthase Associated Gene1 (CsNOA1) Plays a Role in Chilling Stress - Liu, Xingwang; Liu, Bin; Xue, Shudan; Cai, Yanlinq; Qi, Wenzhu; Jian, Chen; Xu, Shuo; Wang, Ting; Ren, Huazhong (Frontiers in Plant Science, 2016)
Nitric oxide (NO) is a gaseous signaling molecule in plants, transducing information as a result of exposure to low temperatures. However, the underlying molecular mechanism linking NO with chilling stress is not well understood. Here, we functionally characterized the cucumber (Cucumis sativus) nitric oxide synthase-associated gene, NITRIC OXIDE ASSOCIATED 1(CsNOA1). Expression analysis of CsNOA1, using quantitative real-time PCR, in situ hybridization and a promoter::β-glucuronidase (GUS) reporter assay, revealed that it is expressed mainly in the root and shoot apical meristem (SAM), and that expression is up-regulated by low temperatures. A CsNOA1-GFP fusion protein was found to be localized to the mitochondria, and ectopic expression of CsNOA1 in the A. thaliana noa1 mutant partially rescued the normal phenotype. Transgenic cucumber plants revealed that the gene is required by seedlings to tolerate chilling stress: constitutive over-expression of CsNOA1 led to a greater accumulation of soluble sugars, starch, and an up-regulation of Cold-regulatory C-repeat binding factor3 (CBF3) expression. Conversely, suppression of CsNOA1 expression resulted in the opposite phenotype and a reduced NO content compared to wild type plants. Additionally, analyses using inhibitors suggested that NO can be synthesized via a CsNOA1 dependent pathway that is independent of the nitrate reductase (NR) pathway.